PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENIPUAN DENGAN MODUS ELECTRONIC CASH DI KEPOLISIAN RESOR KOTA PEKANBARU - Muhammad Yodi Pinto; Dessy Artina; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Online fraud is a crime that often occurs in society, due to the development of technology and information science in the current era of globalization. Especially online fraud with the e-cash mode in which the seller is disadvantaged, where the seller is the one who commits the fraud by taking advantage of the internet banking system. However, until now, law enforcement against online fraud crime has not yet found common ground in revealing the identity of the fraudster, and if allowed to do so, the number of online fraud crimes, especially with the e-cash mode, will increase.This type of research is a sociological legal research, because in this study the author directly conducted research at the location or place studied in order to provide a complete and clear picture of the Pekanbaru City Police, while the population and sample were all parties related to the problems studied in This research, the data sources used, primary data, secondary data and tertiary data, data collection techniques, in this study with interviews and literature study. From the research, there are two main points that can be concluded. first, law enforcement against online fraud using the e-cash mode in the Pekanbaru Police jurisdiction. The two obstacles encountered in law enforcement against online fraud using the e-cash mode in the Pekanbaru Police jurisdiction are in the form of internal factors and external factors. The author's suggestion, first, law enforcement officials should have made preventive efforts by disseminating online fraud that is rife, especially with the e-cash mode by the Pekanbaru Police. Intensive repressive enforcement, namely by creating a special team to take action against perpetrators of online fraud crimes. The police must be more active in terms of law enforcement, that is, not only focusing on reports on law enforcement. Law enforcement officials should have added more specialized personnel to uncover perpetrators of online fraud cases in order to reduce online fraud crime with a similar mode.Keywords: Law Enforcement- Online Fraud Crime Using E-Cash Mode